In Defense of Justice : Joseph Kurihara and the Japanese American Struggle for Equality - Tamura, Eileen (Book collections on Project MUSE., 2013)
As a leading dissident in the World War II concentration camps for Japanese Americans, the controversial figure Joseph Yoshisuke Kurihara stands out as an icon of Japanese American resistance. In emotional, often inflammatory speeches, Kurihara attacked the US government for its treatment of innocent citizens and immigrants. Because he articulated what other inmates dared not voice openly, he became a spokesperson for camp inmates. In this biography, Kurihara's life provides a window into the history of Japanese Americans during the first half of the twentieth century.